A new energy electric bus tire tread rubber and preparation method thereof and tire

By combining rubber and filler in a specific proportion, and undergoing multiple mixing and vulcanization treatments, new energy electric bus tire tread glue is prepared, solving the problem of difficulty in meeting wear resistance, low noise and fatigue and aging resistance in the prior art, and achieving excellent performance and applicability of the tire.

CN118852745BActive Publication Date: 2025-03-21SHANDONG HUASHENG RUBBER +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411130022.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-03-21
Estimated Expiration
2044-08-16

AI Technical Summary

Technical Problem

The prior art is difficult to meet the needs of new energy electric buses for wear resistance, low noise and fatigue and aging resistance.

Method used

A new energy electric bus tire tread rubber is prepared by combining natural rubber, ethylene propylene rubber and nickel-based butadiene rubber in specific proportions, and adding components such as dissolved styrene-butadiene rubber, carbon black, white carbon black and concave and concave and convex rod soil. The tread glue is optimized through multiple kneading and vulcanization treatments.

Benefits of technology

It achieves excellent wear resistance, low noise, fatigue and aging resistance of tires, and can meet the needs of new energy electric buses driving in cities and is suitable for the preparation of tires for electric buses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004997546010000051
    Figure BDA0004997546010000051
  • Figure BDA0004997546010000061
    Figure BDA0004997546010000061
  • Figure BDA0004997546010000071
    Figure BDA0004997546010000071
Patent Text Reader

Abstract

The present application relates to a new energy electric bus tire tread rubber and a preparation method thereof and a tire, belonging to the technical field of tire tread rubber. The tread rubber of the new energy electric bus tire provided in the present application includes the following components by weight: 100 parts of natural rubber, 10-20 parts of EPDM rubber, 40-60 parts of nickel-based butadiene rubber, 5-10 parts of solution-polymerized styrene-butadiene rubber, 20-30 parts of carbon black, 20-40 parts of white carbon black, 5-10 parts of attapulgite, 10-30 parts of paraffin oil, 4-8 parts of antioxidant, 2-4 parts of silane coupling agent, 1-3 parts of zinc oxide, 1-2 parts of stearic acid, 0.2-0.8 parts of accelerator NS, and 3-6 parts of vulcanizing agent; the styrene content in the solution-polymerized styrene-butadiene rubber is 15-20%, and the glass transition temperature is ‑40-‑30°C; the ENB content of the EPDM rubber is 5.0-6.0%, the Mooney viscosity ML (1+4) at 125°C is 70-80, and the ethylene content is 50-60%. The tires made with this tread rubber have excellent wear resistance, low noise, fatigue resistance and aging resistance, and can meet the needs of new energy buses traveling in cities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a new energy electric bus tire tread rubber and a preparation method thereof and a tire, belonging to the technical field of tire tread rubber. Background Art

[0002] Compared with traditional vehicles, new energy electric bus tires have very different performance requirements for tires. For example, since they need to face various sudden situations in the city, sudden stops and starts are the norm for new energy electric buses, so there are higher requirements for tire wear resistance; in addition, since they are driving in the city and passing through residential areas, there are also higher requirements for driving noise. As new energy buses have no engine noise, the noise generated by the tires is more likely to be noticed, so the tires also need to have lower noise; more importantly, due to the large load capacity of the bus, the tires are constantly deformed during operation, and better fatigue and aging resistance are also required.

[0003] However, there is no existing tire product that can simultaneously meet the requirements of new energy electric buses for tire wear resistance, low noise, and fatigue and aging resistance. Therefore, this is a key research direction that urgently needs to be studied. Summary of the invention

[0004] In order to solve the above problems, a new energy electric bus tire tread rubber and a preparation method and a tire are provided. The tire prepared with the new energy electric bus tire tread rubber provided in the present application has excellent wear resistance, low noise, fatigue resistance and aging resistance, and can meet the needs of new energy buses traveling in cities.

[0005] According to one aspect of the present application, a new energy electric bus tire tread rubber is provided. The raw materials of the tread composition of the tread rubber before vulcanization include the following components in parts by weight:

[0006] 100 parts of natural rubber, 10-20 parts of EPDM rubber, 40-60 parts of nickel-based butadiene rubber, 5-10 parts of solution-polymerized styrene-butadiene rubber, 20-30 parts of carbon black, 20-40 parts of white carbon black, 5-10 parts of attapulgite, 10-30 parts of paraffin oil, 4-8 parts of antioxidant, 2-4 parts of silane coupling agent, 1-3 parts of zinc oxide, 1-2 parts of stearic acid, 0.2-0.8 parts of accelerator NS, and 3-6 parts of vulcanizing agent;

[0007] The styrene content of the solution-polymerized styrene-butadiene rubber is 15-20%, and the glass transition temperature is -40 to -30°C; the ENB content of the EPDM rubber is 5.0 to 6.0%, the Mooney viscosity ML (1+4) at 125°C is 70 to 80, and the ethylene content is 50 to 60%.

[0008] In the present application, solution polymerized styrene butadiene rubber and EPDM rubber with specific properties are selected to be combined with nickel-based cis-1,4-dimethyl-1-butyl rubber and natural rubber. The four rubbers are combined in a specific proportion. By controlling the proportion of EPDM rubber and nickel-based cis-1,4-dimethyl-1-butyl rubber, a better quieting effect can be obtained. Moreover, by controlling the styrene content in the solution polymerized styrene butadiene rubber and the proportion used, the tread rubber has better wear resistance.

[0009] Optionally, the particle size of carbon black is 30-40 nm, the iodine absorption value is 60-80 g / kg; the CTAB adsorption specific surface area of ​​white carbon black is 100-120*10 3 m 2 / kg; the average particle size of attapulgite is 30-50μm.

[0010] Optionally, the antioxidant is tetraphenyldiaminomethane.

[0011] Optionally, the silane coupling agent is tert-butyldimethylsilanol.

[0012] Optionally, the vulcanizing agent includes a sulfur vulcanizing agent and a vulcanization accelerator, the sulfur vulcanizing agent is sulfur or a sulfur carrier, and the vulcanization accelerator is one or more of guanidines, sulfenamides, thiurams, and dithiocarbamates.

[0013] Optionally, the raw materials of the tread composition before vulcanization of the tread rubber include the following components by weight:

[0014] 100 parts of natural rubber, 15 parts of EPDM rubber, 50 parts of nickel-based butadiene rubber, 8 parts of solution-polymerized styrene-butadiene rubber, 25-30 parts of carbon black, 20-30 parts of white carbon black, 10-20 parts of paraffin oil, 6-8 parts of antioxidant, 2-4 parts of silane coupling agent, 1-3 parts of zinc oxide, 1-2 parts of stearic acid, 0.2-0.8 parts of accelerator NS, and 3-6 parts of vulcanizing agent.

[0015] According to another aspect of the present application, a method for preparing any of the above-mentioned new energy electric bus tire tread rubbers is provided, and the preparation method comprises the following steps:

[0016] S1, one-stage mixing: natural rubber, EPDM rubber, nickel-based butadiene rubber, solution polymerized styrene-butadiene rubber, carbon black, white carbon black, paraffin oil, silane coupling agent, zinc oxide and stearic acid are put into an internal mixer and mixed for 30 to 50 seconds at a speed of 30 to 50 rpm. The mixture is lifted and pressed every 30 to 45 seconds. When the temperature of the rubber reaches 150°C, the rubber is discharged and flakes are dropped. After being cooled at room temperature, a masterbatch is obtained.

[0017] S2, second stage mixing: the first stage masterbatch obtained in step S1 is put into an internal mixer, mixed at a speed of 30-50 rpm, and the batch is lifted and pressed every 30-45 seconds. When the temperature of the rubber reaches 140°C, the rubber is discharged and the sheets are dropped. After cooling at room temperature, the second stage masterbatch is obtained;

[0018] S. Final mixing: the second-stage masterbatch obtained in step S2, the vulcanizing agent, the accelerator NS and the antioxidant are put into an internal mixer, mixed at 20-30 rpm, and the mixture is lifted and pressed every 20-35 seconds. When the temperature of the rubber material reaches 110° C., the rubber is discharged and the sheets are shed. After being cooled, the tread rubber for the new energy electric bus tire is obtained.

[0019] Optionally, the external temperature vulcanization temperature of the tread rubber of the new energy electric bus tire is 120℃~130℃, of which the vulcanization temperature of the wear sleeve is 120℃~125℃, the vulcanization temperature of the side plate is 125~130℃, and the vulcanization time is 80~100min.

[0020] According to another aspect of the present application, there is provided a use of any of the above-mentioned new energy electric bus tire tread rubbers in the preparation of electric bus tires.

[0021] According to another aspect of the present application, a new energy electric bus tire is provided, and the tread rubber of the tire adopts any of the above-mentioned new energy electric bus tire tread rubbers.

[0022] The beneficial effects of this application include but are not limited to:

[0023] 1. According to the tread rubber of the new energy electric bus tire of the present application, EPDM rubber, nickel-based butadiene rubber and solution-polymerized styrene-butadiene rubber used in combination with natural rubber are combined in a specific proportion, and through experimental screening, a solution-polymerized styrene-butadiene rubber with a styrene content of 15 to 20% and a glass transition temperature of -40 to -30°C, and an EPDM rubber with an ENB content of 5.0 to 6.0%, a Mooney viscosity ML (1+4) of 70 to 80 at 125°C, and an ethylene content of 50 to 60% are selected. The tire prepared with the tread rubber has excellent wear resistance, low noise, fatigue resistance and aging resistance.

[0024] 2. According to the new energy electric bus tire tread rubber of this application, through experimental screening, carbon black with a particle size of 30-40nm, an iodine absorption value of 60-80g / kg, and a CTAB adsorption specific surface area of ​​100-120*10 3 m 2 / kg of white carbon black, and attapulgite with an average particle size of 30-50μm is used as a composite filler. The tire prepared with the tread rubber has excellent wear resistance, low noise, fatigue resistance and aging resistance.

[0025] 3. According to the tread rubber of the new energy electric bus tire of the present application, tetraphenyldiaminomethane is selected as the antioxidant, and tert-butyldimethylsilanol is selected as the silane coupling agent, which has a good synergistic combination effect with other components in the tread rubber. The prepared tire can have good wear resistance, low noise, fatigue resistance and aging resistance.

[0026] 4 According to the new energy electric bus tire tread rubber of the present application, the tire prepared by the tread rubber has good wear resistance, low noise and anti-fatigue and aging resistance, which can meet the requirements of new energy electric buses for frequent emergency stops and starts, low noise and large load capacity and anti-fatigue and aging resistance during driving in the city. It is suitable for preparing tires for electric buses and has a wide range of application scenarios and huge economic value. DETAILED DESCRIPTION

[0027] The present application is described in detail below in conjunction with examples, but the present application is not limited to these examples. Unless otherwise specified, the raw materials and catalysts in the examples of the present application are purchased through commercial channels.

[0028] In this application, the specific compositions of the examples and comparative examples are shown in Table 1 below:

[0029] Table 1 Raw material composition of examples and comparative examples

[0030]

[0031] Table 1 continued

[0032]

[0033] Table 1 continued Table 2

[0034]

[0035] Unless otherwise specified in Table 1, in each embodiment and comparative example, the ENB content of the EPDM rubber used is 5.0-6.0%, the Mooney viscosity ML (1+4) 125°C is 70-80, and the ethylene content is 50-60%; the styrene content of the solution-polymerized styrene-butadiene rubber used is 15-20%, and the glass transition temperature is -40--30°C; the particle size of the carbon black used is 30-40nm, and the iodine absorption value is 60-80g / kg; the CTAB adsorption specific surface area of ​​the white carbon black used is 100-120*10 3 m 2 / kg; the average particle size of the attapulgite used is 30-50 μm. It should be noted that the accelerator NS in the above table is also known as the accelerator TBBS, and its full chemical name is N-tert-butyl-2-benzothiazole sulfenamide; in addition, sulfur is used as the vulcanizing agent in this application. It is known to those skilled in the art that, in addition to sulfur, other sulfur carriers can also be used as vulcanizing agents.

[0036] The present application provides a method for preparing a tread rubber for a new energy electric bus tire, and the preparation method comprises the following steps: S1, first-stage mixing: natural rubber, EPDM rubber, nickel-based butadiene rubber, solution-polymerized styrene-butadiene rubber, carbon black, white carbon black, paraffin oil, silane coupling agent, zinc oxide, and stearic acid are put into an internal mixer and mixed for 30 to 50 seconds at a speed of 30 to 50 rpm, and the treads are lifted and pressed every 30 to 45 seconds. When the temperature of the rubber material reaches 150°C, the rubber material is discharged and flakes are dropped, and the masterbatch is obtained after being cooled at room temperature; S2, second-stage mixing: the rubber material of step S2 is mixed into the masterbatch of step S2, and the masterbatch is mixed into the masterbatch of step S2. The first masterbatch obtained in step S1 is put into an internal mixer, mixed at a speed of 30 to 50 rpm, and the lumps are lifted and pressed every 30 to 45 seconds. When the temperature of the rubber reaches 140°C, the rubber is discharged and the pieces are dropped. After cooling at room temperature, the second masterbatch is obtained; S, final mixing: the second masterbatch obtained in step S2, the vulcanizing agent, the accelerator NS and the antioxidant are put into an internal mixer, mixed at 20 to 30 rpm, and the lumps are lifted and pressed every 20 to 35 seconds. When the temperature of the rubber reaches 110°C, the rubber is discharged and the pieces are dropped. After cooling, the tread rubber of the new energy electric bus tire is obtained. In some embodiments, the external temperature vulcanization temperature of the tread rubber of the new energy electric bus tire is 120°C to 130°C, wherein the grinding sleeve vulcanization temperature is 120°C to 125°C, the side plate vulcanization temperature is 125 to 130°C, and the vulcanization time is 80 to 100 minutes.

[0037] When the performance test of the tread rubber of the embodiment and the comparative example in Table 1 is performed, the preparation method of the tread rubber includes: S1, one-stage mixing: natural rubber, EPDM rubber, nickel-based butadiene rubber, solution-polymerized styrene-butadiene rubber, carbon black, white carbon black, paraffin oil, silane coupling agent, zinc oxide, and stearic acid are put into an internal mixer and mixed for 40 seconds at a speed of 40 rpm, and the lumps are lifted and pressed every 30 seconds. When the temperature of the rubber material reaches 150°C, the rubber is discharged and the sheets are dropped, and the masterbatch is obtained after being cooled at room temperature; S2, two-stage mixing: the masterbatch obtained in step S1 is put into an internal mixer at a speed of 40 rpm. Mixing, lifting and pressing the rubber every 45 seconds, when the rubber temperature reaches 140°C, the rubber is discharged and sliced, and the second-stage masterbatch is obtained after being cooled at room temperature; S, final mixing: the second-stage masterbatch obtained in step S2, the vulcanizing agent, the accelerator NS and the antioxidant are put into an internal mixer, and mixed at 25rpm, and the rubber is lifted and pressed every 25s, when the rubber temperature reaches 110°C, the rubber is discharged and sliced, and the new energy electric bus tire tread rubber is obtained after being cooled; the sleeve vulcanization temperature of the new energy electric bus tire tread rubber is 125°C, the side plate vulcanization temperature is 130°C, and the vulcanization time is 90min.

[0038] The Akron wear, DIN wear index (%), compression fatigue heat generation (℃ / 25min) and heat aging retention rate (%) of the tread rubber products are tested: the compression fatigue heat generation test refers to GB / T1687; in the heat aging retention rate test, the sample is placed in a 150℃ oven for 2 hours to obtain the heat-aged sample, and the elongation at break Eb and stress at break Ts of the sample after aging are measured according to GB / T528. The heat aging retention rate is calculated as follows: Heat aging retention rate = after aging ( Ts×Eb) / before aging (Ts×Eb); In this application, it is considered that the aging retention rate less than 0.6 is poor, the aging retention rate in the range of 0.6-0.8 is good, and the aging retention rate greater than 0.8 is excellent; The obtained tread rubber is used as the tire tread to make tire products, and the same preparation process and materials are used in the production process. However, the noise reduction and quietness performance tests are carried out on the sample tires respectively. The test environment is a highway, the driving speed is 100km / h, and the Xingruida noise tester is used in the car for testing. The original tire is the tire that comes with the car itself. The noise of the original tire is tested first, and then the sample tire is used to replace the original tire for noise testing. The test results are shown in Table 2 below.

[0039] Table 2 Test results of tread rubber performance of examples and comparative examples

[0040]

[0041] Table 2 continued from Table 1

[0042]

[0043] In the test results in Table 2, Akron abrasion and DIN wear index (%) can characterize the wear resistance of the tread rubber, wherein the lower the Akron abrasion value, the better the wear resistance, and the higher the DIN wear index (%) value, the better the wear resistance. Compression fatigue heat generation (℃ / 25min) and thermal aging retention rate (%) can characterize the fatigue resistance and aging resistance of the tread rubber, wherein the lower the compression fatigue heat generation (℃ / 25min) value, the smaller the heat generation, and the larger the thermal aging retention rate (%) value, the better the fatigue resistance and aging resistance of the tread rubber. Noise reduction (dB) can characterize the quietness performance of the tire, and the larger the noise reduction (dB) value, the better the quietness performance of the tire.

[0044] According to the results in Table 2, the tire tread rubber prepared in Examples 1 to 5 of the present application has excellent wear resistance, fatigue resistance and aging resistance, and the prepared tires also have excellent driving quietness performance. According to the results in Table 2, the present application adopts EPDM rubber, nickel-based cis-1,4-butadiene rubber and solution-polymerized styrene-butadiene rubber with specific performance parameters, which can improve the wear resistance of the tread rubber and significantly improve the noise of the tire; the use of carbon black, white carbon black and attapulgite can improve the wear resistance of the tread rubber, and the improvement of the quiet effect of the tire is also relatively obvious; in addition, by selecting tetraphenyldiaminomethane as an antioxidant component to be combined with other components, the heat generation, heat resistance, fatigue resistance and aging resistance are significantly better than those of other antioxidants such as antioxidant RD and antioxidant 4020; in addition, the experimenters found that when tert-butyldimethylsilanol is used as a silane coupling agent and combined with other components such as the rubber matrix and filler of the present application, it has better fatigue resistance and aging resistance than other silane coupling agents such as bis(γ-triethoxysilylpropyl)tetrasulfide, O-(tert-butyldimethylsilane)hydroxylamine.

[0045] In the present application, carbon black, white carbon black and attapulgite with specific parameter performance are selected as fillers for use in combination, which can improve the wear resistance of the tread rubber and also significantly improve the quiet effect of the tire. Before determining the parameters of the carbon black, white carbon black and attapulgite finally selected, because it is necessary to pay special attention to the tensile and tear resistance of the tread rubber, the experimenters found in the preliminary experiments that the parameter performance of carbon black, white carbon black and attapulgite will affect the tensile strength, tensile elongation and tear resistance of the tread rubber. In Table 3 below, the composition of the tread rubber is basically the same as that in Example 1, except that the performance parameters of the raw materials of carbon black, white carbon black and attapulgite are different. For specific differences, see Table 3 below.

[0046] Table 3 Performance parameter selection of carbon black, white carbon black and attapulgite

[0047]

[0048] The experimenters conducted performance tests on the tread rubber prepared from samples 1 to 6 in Table 3. The preparation method of the tread rubber was the same as that of the performance test in Table 2, where the tensile strength and tensile elongation test methods were referenced to GB / T528, and the tear strength test method was referenced to GB / T529. The test results are shown in Table 4 below.

[0049] Table 4 Performance test results of samples 1 to 6

[0050] serial number Tensile strength(MPa) Tensile elongation (%) Tear strength (kN / m) Sample 1 28.6 532 104 Sample 2 27.5 496 98 Sample 3 26.7 503 95 Sample 4 26.9 512 84 Sample 5 26.4 487 87 Sample 6 27.9 408 102

[0051] In Table 4, the larger the tensile strength (MPa) value, the better the tensile resistance of the tread rubber, the larger the tensile elongation (%) value, the better the tensile resistance of the tread rubber, and the larger the tear strength (kN / m) value, the better the tear resistance of the tread rubber. The experimenters found that carbon black with a particle size of 30-40nm and an iodine adsorption value of 60-80g / kg, combined with CTAB adsorption specific surface area of ​​100-120*10 3 m 2 / kg of white carbon black and attapulgite with an average particle size of 30-50μm, when combined with a rubber matrix and a silane coupling agent, etc., have good tensile strength, tensile elongation and tear strength, and better tensile and tear resistance.

[0052] The tread rubber provided in the present application achieves improvements in the wear resistance, fatigue resistance and aging resistance of the tread rubber by optimizing the combination of the rubber matrix, optimizing the combination of fillers, and screening the combination of silane coupling agents and antioxidants. It also has excellent tensile and tear resistance. The prepared tire has good driving quietness and is suitable as a tire for new energy buses running in cities, and has a good market application prospect.

[0053] The above are only embodiments of the present application. The protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the technical ideas and principles of the present application should be included in the protection scope of the present application.

Claims

1. A new energy electric bus tire tread rubber, characterized in that: The raw materials of the tread composition before vulcanization of the tread rubber include the following components by weight: 100 parts of natural rubber, 10-20 parts of EPDM rubber, 40-60 parts of nickel-based butadiene rubber, 5-10 parts of solution-polymerized styrene-butadiene rubber, 20-30 parts of carbon black, 20-40 parts of white carbon black, 5-10 parts of attapulgite, 10-30 parts of paraffin oil, 4-8 parts of antioxidant, 2-4 parts of silane coupling agent, 1-3 parts of zinc oxide, 1-2 parts of stearic acid, 0.2-0.8 parts of accelerator NS, and 3-6 parts of vulcanizing agent; The styrene content in the solution polymerized styrene-butadiene rubber is 15-20%, and the glass transition temperature is -40--30°C; the ENB content of the EPDM rubber is 5.0-6.0%, the Mooney viscosity ML (1+4) at 125°C is 70-80, and the ethylene content is 50-60%; the antioxidant is tetraphenyldiaminomethane; and the silane coupling agent is tert-butyldimethylsilanol.

2. The new energy electric bus tire tread rubber according to claim 1, characterized in that: The particle size of carbon black is 30~40nm, and the iodine absorption value is 60~80g / kg; the CTAB adsorption specific surface area of ​​white carbon black is 100~120*10 3 m 2 / kg; the average particle size of attapulgite is 30~50μm.

3. The new energy electric bus tire tread rubber according to claim 1, characterized in that: The vulcanizing agent is sulfur or a sulfur carrier.

4. The new energy electric bus tire tread rubber according to claim 1, characterized in that: The raw materials of the tread composition before vulcanization of the tread rubber include the following components by weight: 100 parts of natural rubber, 15 parts of EPDM rubber, 50 parts of nickel-based butadiene rubber, 8 parts of solution-polymerized styrene-butadiene rubber, 25-30 parts of carbon black, 20-30 parts of white carbon black, 5-10 parts of attapulgite, 10-20 parts of paraffin oil, 6-8 parts of antioxidant, 2-4 parts of silane coupling agent, 1-3 parts of zinc oxide, 1-2 parts of stearic acid, 0.2-0.8 parts of accelerator NS, and 3-6 parts of vulcanizing agent.

5. The method for preparing the tread rubber of the new energy electric bus tire according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1, one-stage mixing: natural rubber, EPDM rubber, nickel-based butadiene rubber, solution polymerized styrene-butadiene rubber, carbon black, white carbon black, attapulgite, paraffin oil, silane coupling agent, zinc oxide and stearic acid are put into an internal mixer and mixed for 30-50 seconds at a speed of 30-50 rpm. The mixture is lifted and pressed every 30-45 seconds. When the temperature of the rubber reaches 150°C, the rubber is discharged and flakes are dropped. After cooling at room temperature, a masterbatch is obtained. S2, second stage mixing: the first stage masterbatch obtained in step S1 is put into an internal mixer, mixed at a speed of 30-50 rpm, and the batch is lifted and pressed every 30-45 seconds. When the temperature of the rubber reaches 140°C, the rubber is discharged and the sheets are flaked, and the second stage masterbatch is obtained after being cooled at room temperature; S. Final mixing: the second-stage masterbatch obtained in step S2, the vulcanizing agent, the accelerator NS and the antioxidant are put into an internal mixer, mixed at 20-30 rpm, and the mixture is lifted and pressed every 20-35 seconds. When the temperature of the rubber material reaches 110° C., the rubber is discharged and the sheets are shed. After being cooled, the tread rubber for the new energy electric bus tire is obtained.

6. The preparation method according to claim 5, characterized in that The external temperature vulcanization temperature of the tread rubber of new energy electric bus tires is 120℃~130℃, of which the mold sleeve vulcanization temperature is 120℃~125℃, the side panel vulcanization temperature is 125~130℃, and the vulcanization time is 80~100min.

7. Use of the new energy electric bus tire tread rubber according to any one of claims 1 to 4 in the preparation of electric bus tires.

8. A new energy electric bus tire, characterized in that: The tread rubber of the tire adopts the tread rubber of the new energy electric bus tire as claimed in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Pneumatic tyre

    CN103467789A

  • Antiskid tire

    CN104311910A